RNase 7 and Th cytokines synergistically increase the secretion of interleukin-6 from keratinocytes - Shruti Chopra; Janine Siegl; Verena Kopfnagel; Sylvia Dreyer; Franziska Rademacher; Juliane Lokau; Christoph Garbers; Jürgen Harder; Thomas Werfel; Katinka Döhner (Scientific Reports)
Abstract Epidermal keratinocytes are a major source of antimicrobial peptides and proteins. RNase 7 (R7) exhibits antimicrobial and immunomodulatory activities and is upregulated in the lesional skin of atopic dermatitis and psoriasis patients. Here, we performed mRNA microarray analysis to study the influence of R7 on gene expression in human keratinocytes. R7 induced several genes encoding proteins potentially involved in skin integrity and inflammation, including IL-24. Since IL-24 is involved in the pathogenesis of inflammatory skin diseases and since it is induced by IL-6, we further characterized the effect of R7 on IL-6 and IL-24 expression and secretion. R7 increased the release of the cytokines IL-6 and IL-24 by keratinocytes. Using a function-blocking antibody against IL-6 we showed that the R7-induced IL-24 secretion was triggered by IL-6. IL-6 released from R7-stimulated keratinocytes induced STAT3 signaling in target keratinocytes, suggesting a potential pathway resulting in IL-24 induction. Pre-stimulation with IL-17 or IFN-γ, cytokines involved in the pathogenesis of psoriasis, further enhanced R7-induced IL-6 secretion. R7 increased IL-6 secretion mainly from undifferentiated keratinocytes, suggesting that in the epidermis, R7 released from the stratum granulosum may induce expression and secretion of cytokines from basal undifferentiated keratinocytes. In conclusion, our data show that R7 enhances the release of IL-6 in undifferentiated primary keratinocytes, which may have consequences for skin inflammation, defense against pathogens, and wound healing.